2019
DOI: 10.18535/jmscr/v7i12.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Dental Caries on Elementary School Students in Badung Regency – Indonesia

Abstract: Caries, dental and oral disease affects 90% of school-age children. Badung regency occupied fourth position of the populations with dental problem in past 12 months. The data shows only 3.6% of Badung population who behaved properly in brushing. Badung regency economically has the highest local revenues in Bali. The objective of this research is to understand the factors associated with dental caries in primary school students in Badung. This research type is quantitative-qualitative, conducted from July to Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results showed that there was a difference in OHIS scores before and after the training of little dentists at Primary School 1 Kerobokan in Badung Regency, with a p-value 0.000. This study thus concluded that the training of little dentists was effective to escalate dental and oral hygiene for students at SDN 1 Kerobokan, Badung Regency in 2017 (Senjaya, et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…The results showed that there was a difference in OHIS scores before and after the training of little dentists at Primary School 1 Kerobokan in Badung Regency, with a p-value 0.000. This study thus concluded that the training of little dentists was effective to escalate dental and oral hygiene for students at SDN 1 Kerobokan, Badung Regency in 2017 (Senjaya, et al, 2019).…”
Section: Discussionmentioning
confidence: 72%